Assessment of Oral Hygiene Habits among the Dental Students of Bhopal, Madhya Pradesh: A Questionnaire Survey - Jain, Gauravi; Kawadkar, Abhishek; Moidin, Tanveer; Singhal, Vivek; Chouksey, Ankur (Journal of Orofacial Research, 2013)
The aim of conducting this study was to evaluate the oral hygiene attitudes among the budding dentists, and whether progressive dental education and their understanding of preventive dental procedures will improve their commitment toward enhancement of their own oral health attitudes. For this purpose, a cross sectional study was designed for 400 dental students of Bhopal divided into group A (first year and second year) and group B (third year and final year) using a custom formulated objective type of questionnaire to explore their dental health attitudes and behavior based on gender and level of dental education. The complex interplay of factors that shape attitudes and health behaviors, two major influences appear central: culturally determined attitudes/beliefs and behaviors (social norms), and learned experiences. Gender seems to play an important role as data collected show females belonging to both the groups to be having better self-reported health attitudes in majority of investigated areas. The findings of the present study highlighted the relatively poor oral health behavior of Indian dental students, which should be improved in order to serve as a positive model for their patients, family and friends.